Managing inventory in the small and medium entreprises food and beverage industry - Azza Masniza, Sejani; Muhammad Fakhrul, Yusuf; Rashidah, Ramle (2020)
Small and Medium Enterprise (SME) has been recognized as a platform in the economic development in Malaysia where it contributes to more than one-third of the Malaysian economy. SMEs industry help to fulfil the market demand and create more job opportunity. However, many SMEs companies faced a common challenge on their business which disrupted their performance and business continuity. Disruption in maintaining the efficiency of inventory management contribute to significant loss to business performance. Therefore, this research has observed some inventory problems faced by purchasing department at Rasa ABC Enterprise, proposed a solution and evaluated the usefulness/ease of use by using project management steps of initiation, planning, evaluation and analysis. This research has also identified the main issue at Rasa ABC Enterprise using the Ishikawa Diagram and found that the root cause is lack of efficiency in inventory management system. Thus this paper has proposed a solution to use a simple interface, user-friendly, convenient, and cost-effective software. Based on the questionnaires that has been distributed, the workers find the software as useful and easy to be used.